Varieties of the rat race: Working hours in the age of abundance - Jan Behringer; Martin Gonzalez Granda; Till van Treeck (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2022)
We ask why working hours in the rich world have not declined more sharply or even risen at times since the early 1980s, despite a steady increase in productivity, and why they vary so much across rich countries. We use an internationally comparable database on working hours (Bick et al., 2019) and conduct panel data estimations for a sample of 17 European countries and the United States over the period 1983-2019. We find that high or increasing top-end in- come inequality, decentralized labor relations, and limited government provision of education and other in-kind services contribute to long working hours. Our results are consistent with the hypothesis that upward-looking status comparisons in positional consumption ("Veblen effects") contribute to a "rat race" of long working hours that is more or less pronounced in different varieties of capitalism.
Keywords: D31; J20; P16; P50; 330; Working hours; Veblen effects; income inequality; varieties of capitalism